ECOLOGICAL AND SYSTEMATIC CHARACTERISTICS OF BACILLARIOPHYTA IN THE WATER BODIES OF THE CITY OF CHIRCHIK (World Bulletin of Management and Law, 2023)
This article deals with the issues of species diversity, ecological and systematic characteristics of Bacillariophyta - Diatoms in the reservoirs of Chirchik, the formation of theoretical knowledge and practical skills in conducting research in the field of taxonomy, ecology of algae, studying the cycles of their development, the formation of skills for conducting field and laboratory algological research, the use of high-tech laboratory equipment in the course of solving scientific tasks in the field of algology, the formation of professional training for independent scientific, research and pedagogical activities, the essence of modern methods of collecting quantitative and highquality samples of plankton, periphyton and benthic algae, office processing of material, taxonomic and morphometric processing of samples